(untitled) - Shurtleff, William (Brookline, Mass, 1975)
Part i: Tofu: Food for Mankind; Part II: Cooking with Tofu: Recipes from East and West; Part III: Japnese Farmhouse Tofu: Making Tofu for More and More People; Part IV: The Practice of Making Tofu: The Traditional Tofu Shop
Keywords: Cooking,Nấu ăn; Soybeans,Đậu nành